Determinants of Audit Report Lag: Evidence from Commercial Banks in Indonesia - Septiani Wulandari; Zuni Barokah (The Indonesian Journal of Accounting Research, 2022)
This research aims to test and analyze the determinants of audit report lag. This research uses purposive sampling and includes commercial banking companies listed on the Indonesian Stock Exchange during 2017-2019. Using multiple regression analysis methods, the study found that companies have shorter ARL if they have an audit committee with members with financial expertise or are audited by auditors with industry specialization. These findings indicate that companies with an audit committee with financial expertise or those audited by auditors with industry specialization produce a shorter audit process. However, this research did not find evidence of the influence of the audit committee size, the number of audit committee meetings, and the reputation of independent auditors on ARL